2015
DOI: 10.1055/s-0035-1558405
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Endometrial Physiology

Abstract: Human endometrial mucosa is a dynamically remodeling tissue, undergoing cyclical morphologic and functional changes in response to fluctuating sex steroid hormones each menstrual cycle during a woman's reproductive life. Postmenopausal endometrium responds similarly to exogenous estrogen. Cyclical endometrial regeneration also occurs in nonmenstruating rodents, although to a lesser extent. The recent identification of rare populations of endogenous epithelial progenitor cells, mesenchymal stem/stromal cells (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Some of these mesenchymal/ mesothelial cells of the peritoneal cavity (48), of the mesothelial repair after surgery (126) and in endometrium and endometriosis (127)(128)(129)(130)(131) are directly derived from bone marrow. Endometriosis could develop from stem cells in the endometrium (132,133) or in the peritoneal cavity (29,(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144), possibly induced by genetic changes (60). Recently a specific cell in the endometrium called pale cell (145,146), because of their appearance, was speculated to be involved in endometriosis and adenomyosis development.…”
Section: Development Of (Deep) Endometriosis: What Is the Original Cell?mentioning
confidence: 99%
“…Some of these mesenchymal/ mesothelial cells of the peritoneal cavity (48), of the mesothelial repair after surgery (126) and in endometrium and endometriosis (127)(128)(129)(130)(131) are directly derived from bone marrow. Endometriosis could develop from stem cells in the endometrium (132,133) or in the peritoneal cavity (29,(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144), possibly induced by genetic changes (60). Recently a specific cell in the endometrium called pale cell (145,146), because of their appearance, was speculated to be involved in endometriosis and adenomyosis development.…”
Section: Development Of (Deep) Endometriosis: What Is the Original Cell?mentioning
confidence: 99%
“…Epithelial progenitor cells in endometrial unicellular suspensions obtained from hysterectomy tissue to allow testing of basal glands; is clonogenic cells [17]. Identification of epithelial progenitor markers will provide an opportunity to investigate its role, endometrial regeneration in normal cycling endometrium, and gynecological diseases associated with abnormal epithelial proliferation such as endometriosis, endometrial cancer and adenomyosis [3]. The monthly regeneration of the human endometrium, it is almost completely resected after the parturition and in postmenopausal women taking estrogen-based hormone replacement therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity and weak clonogenicity making single cell culture impractical restrict the researchs of the endometrial SP. However, much proof suggests that endometrial stem/progenitor cells are enriched in the SP fraction [20,3]. Although many studies have been achieved on endometrial cells derived from bone marrow, most have not identified the type of bone marrow cells that contribute to the endometrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endometrium of the uterus in mammals is capable of high and periodic self-renewal regeneration. Also, reconstruction of the endometrium after parturition and rapid proliferation and restoration indicates that the endometrium can be a rich source of MSCs [17]. On the other hand, larger amounts of MSCs are needed for use in clinical and experimental applications than the starting population isolated MSCs which must be expanded in vitro .…”
Section: Introductionmentioning
confidence: 99%